The Role Of The Uswatun Hasanah Mosque Zakat Institution In Improving The Welfare Of Mustahiq In Pahayu Jaya Village - Kumalahayati, Nur; Rahmawati, Putri (Nuban Jagadhita Centre, 2025)
Purpose: This study aims to analyze the role of the Uswatun Hasanah Mosque Zakat Institution in improving the welfare of mustahiq in Pekon Pahayu Jaya, West Lampung Regency. Methodology: The study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. Findings: The results show that this institution runs three main programs, namely disaster relief, education, and social assistance, which have a direct impact on the lives of mustahiq. Although still limited in terms of reach, this institution has contributed to improving the economic conditions of the poor. However, zakat management still faces cultural challenges, namely the tendency of muzakki to distribute zakat directly without going through institutions. This study recommends the need for public education and increased institutional transparency to strengthen public trust in zakat institutions. These findings emphasize the importance of strengthening mosque-based zakat institutions in supporting community empowerment at the local level.